Exploring the health care utilization of children and youth in the care of child welfare: a retrospective matched cohort study. (26th November 2021) - Breneol, Sydney; Rose, Heather; Brown, Marion; Andreou, Pantelis; Bishop, Andrea; Mitchell, Carolyn
Abstract: Background: Children and youth whose lives intersect with child welfare systems are amongst the most vulnerable paediatric populations. Despite the increased rates of chronic conditions, these children and youth often experience unmet health care needs. Objectives: To examine patterns of health care utilization from birth for children and youth in the care of a child welfare authority. Methods: This retrospective matched cohort design study examined children/youth aged 0–18 who had visited a paediatric tertiary care facility from 2016 April 1 to 2017 March 31 and had "social worker" documented as their guardian. A control cohort was matched based on age and sex. Primary outcomes of interest included primary health care, emergency, outpatient, and inpatient visits. Visits for immunizations, physiological development, well-baby checks, mental health, and oral health were also examined. Results: A total of 200 cases and 200 controls were included in our cohort. No statistically significant differences were found between primary care visits, well-baby checks, inpatient admissions, outpatient mental health visits, or immunizations for children in care in comparison to their controls. There was a significant difference in oral health visits, lack of physiological development, and emergency department visits for children in care when compared to their controls. Conclusions: Our study revealed disparities in health care utilization amongst children in the care of child welfare in comparison to those who are not, highlighting the need for improved practice, policy, and research initiatives. A collaborative data collection/sharing system is needed to identify and track the health care of this vulnerable population. Lay Summary: Children and youth whose lives intersect with child welfare systems are amongst the most vulnerable pediatric populations. Despite the increased rates of chronic health conditions, these children and youth often experience unmet health care needs. Using a retrospective matched cohort design, we sought to examine patterns of health care utilization from birth to age 18 for children and youth in the care of a child welfare authority in comparison to children/youth who were not in the care of child welfare. No statistically significant differences were found between primary care visits, well-baby checks, inpatient admissions, outpatient mental health visits, or immunizations for children in care when compared to their counterparts not in care. There was a significantly higher number of oral health visits, physiological development concerns, and emergency department visits for children in care when compared to their controls. Our study revealed differences in health care use amongst children in the care of a child welfare in comparison to those who are not, highlighting the need for improved practice, policy and research initiatives. A collaborative data collection and sharing system is needed to help accurately identify and track the health care use of this vulnerable population.